Posterior left ventricular aneurysm - Burstin, Jacobo; Nozar, José; Goller, Wolfgang; Fernández Perdomo, Gonzalo (Cirugía del Uruguay, 1979)
The author presents a case of posterior ventricular aneurysm treated by resection and closure of ventriculotomy over a Teflon strip.